2015
DOI: 10.1007/s13204-015-0452-4
|View full text |Cite
|
Sign up to set email alerts
|

Detection of heavy metals (Cu+2, Hg+2) by biosynthesized silver nanoparticles

Abstract: Here, we are reporting two methods for detection of Cu ?2 ion and Hg ?2 ions using biosynthesized silver nanoparticles. The detection of Cu ?2 ion was based on changes in absorbance resulting from complex formation of the metal ion. Various concentrations of Cu ?2 ion were used to test the linearity and sensitivity of the method. A new peak at around 770 nm, in addition to the peak of the AgNP at 406 nm, was observed in each case (above 20 lM). With the increase of concentration of Cu ?2 ion solution, the abso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(34 citation statements)
references
References 35 publications
3
27
0
Order By: Relevance
“…Due to the tunable size and distance-dependent optical properties of metallic nanoparticles, they have been preferably employed for the detection of heavy metal ions in polluted water systems [ 145 , 146 ]. The advantages of using metal NPs as colorimetric sensors for heavy metal ions in environmental systems/samples include simplicity, cost effectiveness, and high sensitivity at sub ppm levels.…”
Section: Environmental Remediation Applicationsmentioning
confidence: 99%
“…Due to the tunable size and distance-dependent optical properties of metallic nanoparticles, they have been preferably employed for the detection of heavy metal ions in polluted water systems [ 145 , 146 ]. The advantages of using metal NPs as colorimetric sensors for heavy metal ions in environmental systems/samples include simplicity, cost effectiveness, and high sensitivity at sub ppm levels.…”
Section: Environmental Remediation Applicationsmentioning
confidence: 99%
“…Recent studies show that nanoparticles can be widely used as heavy-metal detectors. Among others, silver [ 10 11 ], gold [ 12 ] and also magnetic nanoparticles [ 13 – 14 ] usually doped with other elements (e.g., Ca, Mn) [ 15 16 ] have been tested for this purpose. Therefore, detailed studies on adsorption efficiency on doped magnetite nanoparticles are very interesting and innovative in order to understand the importance of core composition and surface modification.…”
Section: Introductionmentioning
confidence: 99%
“…The possible mechanism of the colorimetric assay for sensing Pt +2 is yet unknown but the methods of determination is reported to rely on their unique size and inter-particle distance-dependent absorption spectra and color change of the solution [24]. As per the previous studies that demonstrated the heavy metal detection by AgNPs, the bacterial proteins responsible for reduction of silver, its stabilization and the peptide linkage (—CONH—) may be responsible for formation of coordination complex with Pt +2 [25].…”
Section: Resultsmentioning
confidence: 99%